Inflammatory biomarkers in HIV-infected children hospitalized for severe malnutrition in Uganda and Zimbabwe. (15th July 2019) - Prendergast, Andrew J.; Berejena, Chipo; Pimundu, Godfrey; Shonhai, Annie; Bwakura-Dangarembizi, Mutsa; Musiime, Victor; Szubert, Alexander J.; Cook, Adrian D.; Spyer, Moira J.; Nahirya-Ntege, Patricia; Kekitiinwa, Adeodata; Gibb, Diana M.; et al.
Abstract : Objectives: A proportion of HIV-infected children with advanced disease develop severe malnutrition soon after antiretroviral therapy (ART) initiation. We tested the hypothesis that systemic inflammation underlies the pathogenesis of severe malnutrition in HIV-infected children. Design: Cross-sectional laboratory substudy in 613 HIV-infected children initiating ART in Uganda and Zimbabwe. Methods: We measured C-reactive protein (CRP), TNFα, IL-6 and soluble CD14 by ELISA in cryopreserved plasma at baseline (pre-ART) and week-4 (children with severe malnutrition only). Independent associations between baseline biomarkers and subsequent hospitalization for severe malnutrition were identified using multivariable fractional polynomial logistic regression. Results: Compared with children without severe malnutrition ( n  = 574, median age 6.3 years, median baseline weight-for-age Z -score −2.2), children hospitalized for severe malnutrition post-ART ( n  = 39, median age 2.3 years, median baseline weight-for-age Z -score −4.8) had higher baseline CRP [median 13.5 (interquartile range 5.5, 41.1) versus 4.1 (1.4, 14.4) mg/l; P  = 0.003] and IL-6 [median 9.2 (6.7, 15.6) versus 5.9 (4.6, 9.3) pg/ml; P  < 0.0001], but similar overall TNFα, soluble CD14 and HIV viral load (all P  > 0.06). In a multivariable model, higher pre-ART IL-6, lower TNFα and lower weight-for-age were independently associated with subsequent hospitalization for severe malnutrition. Between weeks 0 and 4, there was a significant rise in CRP, IL-6 and soluble CD14, and fall in TNFα and HIV viral load in children hospitalized for severe malnutrition (all P  < 0.02). Conclusion: Pre-ART IL-6 and TNFα were more strongly associated with hospitalization for severe malnutrition than CD4 + cell count or viral load, highlighting the importance of inflammation at the time of ART initiation in HIV-infected children.